2018
DOI: 10.3390/app8081386
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphene Nanoplatelet and Silver Nanoparticle on the Rheological Properties of Water-Based Mud †

Abstract: Water-based mud is known as an environmental-friendly drilling fluid system. The formulation of water-based mud is designed to have specific rheological properties under specific oil field conditions. In this study, graphene nanoplatelet and silver nanoparticle (nanosilver) were added to a water-based mud formulation in which they act as drilling mud additives. Rheological properties measurements and filtration tests were conducted for evaluating the influence of the added nanoparticles. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Husin et al reported a torque reduction of 20% with the use of a lubricant concentration of only 1% [ 149 ]. Some of the conventionally used lubricants in drilling fluids include oils, graphite, powder, surfactant, and soaps [ 150 ].…”
Section: Effects Of Nanomaterials In Drilling Fluidsmentioning
confidence: 99%
“…Husin et al reported a torque reduction of 20% with the use of a lubricant concentration of only 1% [ 149 ]. Some of the conventionally used lubricants in drilling fluids include oils, graphite, powder, surfactant, and soaps [ 150 ].…”
Section: Effects Of Nanomaterials In Drilling Fluidsmentioning
confidence: 99%
“…The American Petroleum Institute (API) has given particular specifications and procedures which provide difficulty for newly made-up nanocomposites and base fluid formulations due to the fact of their different properties, process parameters, and other requirements [ 147 ]. It is also recognized that preparation protocols and key measurements of these nanocomposites find difficulty in the combination with graphene-based materials [ 148 ]. In this regard, more research emphasis on graphene-derived materials could be a promising substitute.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…The nanocomposite only created slight variations on the rheological parameters of the water-based muds and showed a significant filtration control performance. The paper by Husin et al [4], on the other hand, applied graphene nanoplatelets and silver nanoparticles (NPs) to a water-based mud. They demonstrated that the graphene nanoplatelet and the silver NPs increased the plastic viscosity by up to 89.2% and 64.2%, respectively, while both the yield point and the fluid loss values were reduced.…”
Section: Nanotechnology and Nanomaterials Applications In The Oil Andmentioning
confidence: 99%